2022
DOI: 10.3390/s22155547
|View full text |Cite
|
Sign up to set email alerts
|

Image-Based Phenotyping for Non-Destructive In Situ Rice (Oryza sativa L.) Tiller Counting Using Proximal Sensing

Abstract: The increase in the number of tillers of rice significantly affects grain yield. However, this is measured only by the manual counting of emerging tillers, where the most common method is to count by hand touching. This study develops an efficient, non-destructive method for estimating the number of tillers during the vegetative and reproductive stages under flooded conditions. Unlike popular deep-learning-based approaches requiring training data and computational resources, we propose a simple image-processin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Fertilizer (15,6,20,11,7 g/m 2 of N, P, K, Mg, and Ca, respectively) was added before sowing. Each plot contained four plants of one accession.…”
Section: Field Experimentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Fertilizer (15,6,20,11,7 g/m 2 of N, P, K, Mg, and Ca, respectively) was added before sowing. Each plot contained four plants of one accession.…”
Section: Field Experimentsmentioning
confidence: 99%
“…For instance, remote sensing using unmanned aerial vehicles (UAVs) has become a prominent approach to data collection in the field [4, 5]. Such UAVs are equipped with various sensors, including RGB cameras [6, 7], multispectral cameras [8], and Light Detection and Ranging (LiDAR) devices [9, 10]. Although RGB cameras are commonly employed because of their ease of use, affordability, and minimal maintenance requirements, multispectral cameras are becoming popular for measuring vegetation indices associated with growth and yield [11].…”
Section: Introductionmentioning
confidence: 99%
“…While the system is capable of obtaining real-time plant images and making predictions, the accuracy of its classification model for plant diseases remains a challenge. Yuki et al proposed a straightforward image processing pipeline that adheres to the empirical principle of the simultaneous emergence of leaves and tillers in rice morphogenesis [14]. The team utilized an unmanned aerial vehicle to capture field images at very low flight altitudes.…”
Section: Introductionmentioning
confidence: 99%
“…It is obvious that image-based phenotyping covers the shortage of these above methods. A few studies have shown that leaf morphological traits can be accurately estimated by the image-based phenotyping [12][13][14].…”
Section: Introductionmentioning
confidence: 99%